GERAKAN ALIANSI LAKI-LAKI BARU: MEMBONGKAR KONSTRUKSI MASKULINITAS UNTUK MEWUJUDKAN KEADILAN GENDER - Ira Larasati; Pudji Astuti (Journal of Politic and Government Studies, 2019)
This research aims to obtain in-depth information about the New Men Alliance’s movements in dismantling the construction of masculinity in Indonesia as an effort to manifest the gender equity. The research method used in this study is descriptive qualitative. The instruments that used in this research are document studies and interviews conducted to activists of the New Male Alliance. The results of this study shows that male involvement in the feminist movement is needed and has good impact on efforts to transform men from the traditional perspective of the construction of masculinity. The movement carried out by the New Men's Alliance is a movement that focuses on efforts to transform men and form a "new male identity" that is in line with the values of equality and justice. In carrying out its movement, the New Men's Alliance has a very dynamic approach that depends on the reality at hand. Broadly speaking, the strategies carried out by the Alliance of New Men are divided into two,that is: 1) doing collective action in real by face to face between the allies, 2) utilizing digital media and online media to spread ideas about the importance of male involvement in efforts to gain gender equity. The work carried out by the Alliance of New Men is voluntary-based, which emphasizes values and principles as the identity of the New Male Alliance. Keywords: Social Movements, New Male Alliance, Gender Equity